Sociodemographic, clinical profile and factors related to Traumatic Brain Injury - Aparecida Fernandes, Larissa; Waters, Camila (Seven Editora, 2023)
Introduction: Traumatic brain injury (TBI) is defined as all aggression that can cause anatomical injury or functional involvement of the scalp, skull bones, meninges, brains. Traffic accidents, motorcycle accidents, falls and urban violence are among the main occurrences of trauma, more common in evils. The mechanism of trauma can be penetrating, or blunt and brain lesions can be classified as primary and secondary. Trauma is a preventable public health problem, with high morbidity rates in an economically and socially active age group. Objective: Identify, in the scientific literature, articles describing the epidemiological profile and factors related to traumatic brain injury. Methods: Narrative and descriptive bibliographic research, using specific health sciences descriptors: craniocerebral trauma; cerebrovascular trauma; traumatic brain injuries; closed head trauma; penetrating head trauma, which were crossed with the general descriptors: health profile, epidemiology. Complete scientific articles, available in full, free of charge, written in the Brazilian Portuguese (Brazil) and published from January 2017 to April 2022 were included. Results: the material this research of 11 articles, it is possible to identify that the highest frequency of TBI occurs in victims aged between 20 and 30 years, demonstrating to affect economically active young people on society. Males had the most frequent occurrence of TBI in all articles analyzed, ranging from 76.2% to 94.0%. Females, on the other hand, had a variation from 6.0% to 23.8%. With about to the severity of the TBI, the mild TBI ranged from 4.1% to 38.3%, the moderate TBI ranged from 4.1% to 92.7% and the severe TBI ranged from 1.6% to 91.8%. Regarding the etiology of TBI, motorcycle accidents predominated (19.0% to 72.5%), followed by a fall (3.4% to 25.0%), hit-and-run (3.6% to 18.0%), car accidents (2.2% to 16.4%), physical aggression (2.4% to 11.0%), tool using a firearm (2.3% to 11.0%), and bicycle accidents (1.0% to 4.1%). Regarding clinical manifestations, the lowering of the level of consciousness prevailed, followed by headache, periorbital hematoma, vomiting, otorrhagia, convulsion, anisocoria and rhinorrhea. Regarding the type of treatment, the conservative presented a frequency of 31.1% to 86.4% and the surgical presented a frequency of 9.7% to 68.8%. The mean hospital stay ranged from 6.2 to 11 days and the frequency of death ranged from 9.5% to 38.6%. Conclusion: Regarding the epidemiological profile of TBI in Brazil, in the years 2017 to 2022, young male individuals prevailed, victims of motorcycle accidents, manifested by lowering the level of consciousness, being performed conservative treatment and remaining treatment and leaving for one to two hospitalized weeks in the hospital. DOI: https://doi.org/10.56238/tfisdwv1-025